Evaluation of Budgeting Procedure Implementation from the Perspective of Regulatory Compliance (Case Study of Banguntapan Village) - Fatmawati, Fatmawati; Milanesha, Musyaffa Iltsar; Ardhani, Naila Fidelya; Malika Dewi, Abelva (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Transparent and accountable management of village finances is a crucial aspect of local governance; however, in practice, it still faces challenges, including potential procedural non-compliance and constraints arising from drastic budget cuts in the field. This study aims to evaluate the implementation of the Village Budget Revenue and Expenditure (APBKal) procedures in Banguntapan Village from the perspective of compliance with Minister of Home Affairs Regulation (Permendagri) Number 20 of 2018 and Regent of Bantul Regulation Number 59 of 2022. A descriptive qualitative approach with a case study method was applied in this research through data collection from semi-structured interviews with the Village Secretary, analysis of planning and financial documents, and literature review.